2023
DOI: 10.2340/actadv.v103.4441
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Costs in Alopecia Areata: A Cross-Sectional Study in German-speaking Countries

Abstract: Alopecia areata is a common skin disease which is associated with psychosocial and financial burden. No curative therapy exists and, hence, affected persons resort to self-financed cosmetic solutions. However, studies on the economic impact of alopecia areata on individuals are limited. To estimate annual individual out-of-pocket costs in persons with alopecia areata, a cross-sectional study using a standardized online questionnaire was performed in Germany, Austria and Switzerland. A total of 346 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The financial burden of alopecia is underexplored in the literature, with most studies focusing on alopecia areata. 2,3,5 We found that individuals diagnosed with alopecia experience additional financial costs for treating or concealing their condition. Higher out-of-pocket expenses arose from initially seeking nondermatologist providers, purchasing OTC products, and utilizing camouflaging agents, such as cranial prostheses.…”
Section: Dear Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The financial burden of alopecia is underexplored in the literature, with most studies focusing on alopecia areata. 2,3,5 We found that individuals diagnosed with alopecia experience additional financial costs for treating or concealing their condition. Higher out-of-pocket expenses arose from initially seeking nondermatologist providers, purchasing OTC products, and utilizing camouflaging agents, such as cranial prostheses.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Alopecia, an often chronic hair loss condition, impacts individuals' self-identity, psychological well-being, and quality of life, and may incur considerable financial costs. [1][2][3][4] Patients frequently turn to alternative therapies, such as over-the-counter (OTC) products, camouflaging agents, or cranial prostheses. [1][2][3] This study explores the financial burden experienced by alopecia patients.…”
Section: Dear Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alopecia areata (AA) is a chronic immunological condition characterized by hair loss on the scalp and/or body. The effectiveness of medical treatments for AA is inconsistent and unpredictable (Strazzulla et al, 2018), and in many instances, insurers are unwilling to reimburse for the cost of treatments and psychosocial coping modalities (e.g., Ezemma et al, 2023; Kullab et al, 2023) as AA has traditionally been recognized as a medically benign, cosmetic condition. However, an “it’s just hair” perspective fails to consider the elevated levels of suffering and significant impact on quality of life (QOL) reported by many living with AA (Rencz et al, 2016).…”
Section: Coping With Alopecia Areatamentioning
confidence: 99%
“…A third cross-sectional study utilizing a standardized online survey was conducted in Germany, Austria, and Switzerland [37]. It was completed by 346 AA patients (95.1% women, mean age 38.5 ± 11.6 years) and showed that average extra spending on daily essentials was EUR 1248 per person annually.…”
Section: Personal Financial Costs Of Aamentioning
confidence: 99%